Determinant Analysis of Trigger Risk of Death of Father Because of Non-Communicable Diseases in the Family - Miftahul Munir (Universitas Airlangga, 2020)
Introduction: The tendency of non-communicable diseases is chronic, with the impact of disability including permanent disability. The purpose of this study is to analyze the determinants of the risk of father's death due to non-communicable diseases in families in Semanding District, Tuban Regency.Methods: This type of research is observational analytic with case control design. Using cluster sampling, 437 samples were taken. In the second stage, the sample was taken by determining the highest non-communicable diseases in the family, 0.82%, then the sample size was 182 with a case group of 82 (the highest non-communicable diseases) and a control of 100 (the father’s non-communicable diseases risk).Results: Data collection was done by interview. OR = 5,863 95% CI 3,087-11,136) with, consumption of foods high in excess salt (OR = 7,653 CI 95 % 3,951-14,821), consumption of food and drink high in excess sugar (OR 5, 582 CI 95% 2.9478-10.57) smoking (OR = 4.849 CI 95% 2.545-9.238).Conclusion: The health classification of respondents, namely the father as the head of the family suffering from non-communicable diseases, as the highest cause of death in the group of fathers at risk is smoking. The highest sufferers of non-communicable diseases is as the head of the family in the district. The highest in Kab.Tuban in 2018 is primary hypertension. This triggers the risk of death of the father because of the highest non-communicable diseases in families in the district. Notable in Kab. Tuban in 2018 is the lack of consumption of fruits and vegetables, consumption of foods high in excess salt, consumption of foods / drinks high in excess sugar and smoking.